Waste-to-wealth in ASEAN countries: A case on e-waste generation from mobile phone. Issue 1 (October 2021) - Ismail, H; Hanafiah, M M
Abstract: The aim of this study was to evaluate the potential economic value of e-waste generation in ASEAN countries. The data used in this study was based on various reports. As the reliable information on e-waste generation in ASEAN countries is scarce, the study only evaluated the potential economic value of e-waste generation from mobile phone. The results showed that the potential economic value of e-waste from mobile phone around the world was valued at US 18, 545.27 million. For ASEAN countries, it was valued at US 2, 019.06 million, higher than 27 developed countries in European Union that valued at US 1, 286.59 million. Currently, apart from the ineffective implementation of e-waste regulation, the lack of reliable information and data to estimate e-waste generation and its future projection was a common problem faced by ASEAN countries that impending the development of sustainable e-waste management. Therefore, the potential economic value of e-waste generation in ASEAN countries could be higher, if various other products were included in the analysis with a reliable information and data. Finally, some recommendation was made that includes the need a thorough intergovernmental cooperation and collaboration among ASEAN countries in order to reap a potential economic benefit from continuously growing e-waste in this region.